Dynamic of solitary wave solutions in some nonlinear pseudoparabolic models and Dodd-Bullough-Mikhailov equation - Ilhan, O. A.; Bulut, H.; Sulaiman, T. A.; Baskonus, H. M. (Indian Assoc Cultivation Science, 2018)
In this study, the modified exp (-Phi(eta))-expansion function method is used in constructing some solitary wave solutions to the Oskolkov-Benjamin-Bona-Mahony-Burgers, one-dimensional Oskolkov equations and the Dodd-Bullough-Mikhailov equation. We successfully construct some singular solitons and singular periodic waves solutions with the hyperbolic, trigonometric and exponential function structures to these three nonlinear models. Under the choice of some suitable values of the parameters involved, we plot the 2D and 3D graphics to some of the obtained solutions in this study. All the obtained solutions in this study verify their corresponding equation. We perform all the computations in this study with the help of the Wolfram Mathematica software. The obtained solutions in this study may be helpful in explaining some practical physical problems.
Keywords: The MEFM; The Oskolkov-Benjamin-Bona-Mahony-Burgers; The one-dimensional Oskolkov equation; The Dodd-Bullough-Mikhailov equation; The singular soliton solution; The singular periodic wave solution